The properties of ITO/ZnO antireflective conducting substrate prepared by R.F. magnetron sputtering for DSSCs application: article - Abdul Majid, Mashitah (2012)
In this work, the properties of anti-reflective ZnO (arcZnO) thin film deposited on ITO conducting substrate by rfmagnetron sputtering is presented. The ITO/arc-ZnO conducting substrate with blocking layer capabilities has been designed using step-down interference coating structure based on double layer antireflection coating (DLAR). The Raman spectroscopy result revealed a mixed-oriented type of crystalline structure between ITO and ZnO with 601.74cm-1 shift, and 1125.16cm-1 shift. The antireflection behavior of multilayer ITO/arc-ZnO is evidence with the presence of two maximum peaks overshoots at 370–500nm and 600-800nm range while eliminating approximately 92% reflectance, hence contributes to higher overall transmittance (≥ 80%) in the mid-wavelength region. The sheet resistance decreases from 62.06897Ω/sq to 33.02552Ω/sq with increase the RF power from 30W to 120W. These results demonstrate that the multilayered ITO/arc-ZnO with tailored refractive index substrate is a realistic approach for higher overall transmittance with good stability in electrical properties, prolonged with an added capability of suppressing back electron transfer that is foreseen suitable for dye sensitized solar cell application.